HEPATOPROTECTIVE EFFECT OF CURCUMIN IN CHRONIC HEPATITIS - Marinda, Ferina Dwi (Majority, 2014)
Abstract Chronic hepatitis is a serious and common problem in the world especially in Indonesia. Persons with chronic hepatitis often lead to cirrhosis and about 20 to 30% of people become hepatocellular carcinoma. Treatments of chronic hepatitis are decreasing liver inflammation by treating or suppressing the virus replication, so liver damage can’t develop. There is no optimal therapy until now, so scientist try an alternative therapy such as herbal therapy. One of the herbal medicine is turmeric to treat liver disease. An active chemical component of curcuma species is curcumin as hepatoprotective. The effects of curcumin as antioxidant are to scavange superoxide ion, to break chain between superoxide ion (O2-) and to prevent the liver damage. Curcumin increases gluthation S-transferase (GST) and inhibits some of the proinflammation, gen expression and hepatitis B virus replication via down-regulation of PGC-1α, so it concluded that curcumin can be used as an alternative hepatoprotector of patients with chronic hepatitis. Keywords: curcumin, hepatoprotective, turmeric Abstrak Hepatitis kronis merupakan masalah besar di dunia termasuk di Indonesia. Bila seseorang terkena hepatitis kronis dapat berkembang progresif menjadi sirosis hati dan akhirnya kanker hati pada 20-30% kasus. Tujuan pengobatan hepatitis kronis adalah mengurangi peradangan hati dengan menghilangkan atau menekan replikasi virus penyebab, sehingga kerusakan hati tidak berlanjut. Sampai saat ini belum ada terapi yang optimal, maka para ahli mencoba terapi alternatif seperti terapi herbal. Salah satu obat herbal yang sering digunakan dalam mengobati gangguan hepar adalah temulawak. Bahan aktif dari berbagai spesies curcuma tersebut adalah curcumin yang berperan sebagai hepatoprotektif. Efek kurkumin sebagai antioksidan yang mampu menangkap ion superoksida dan memutus rantai antar ion superoksida (O2-) sehingga mencegah kerusakan sel hepar. Curcumin juga mampu meningkatkan Gluthation S-Transferase (GST) dan mampu menghambat beberapa faktor proinflamasi , ekspresi gen dan replikasi virus hepatitis B melalui down-regulation dari PGC-1α, sehingga dapat disimpulkan bahwa curcumin dapat dijadikan alternatif hepatoprotektor pada pasien hepatitis kronis. Kata kunci: curcumin, hepatoprotektif, temulawak